Opportunities for Diversification of Processed Nutmeg as an Effort to Improve the Community's Economy on Saparua Island - Hendri Dony Hahury; Ariviana L Kakerissa; Fredy H Louhenapessy (MediaTrend, 2023)
Product diversification efforts can be used as a strategy to develop knowledge and skills as well as an alternative source of income for community households. The product diversification can be more optimal if it is supported by the availability of raw material sources located close to the community and wide market potentials so as to lower production costs incurred. This study uses a mixed method with a sequential exploration approach. This method begins with the use of qualitative method, followed by the quantitative method and interpretation. This study puts more emphasis on the qualitative analysis. Respondents of this study include farmers, community leaders and the government of Negeri Booi. Findings reveal that the most suitable diversifications of nutmeg products in Negeri Booi were in the form of nutmeg cider business and nutmeg juice business. Both of these businesses were supported by the availability of abundant raw materials, not too big business capital, and wide marketing potentials. This phenomenon was also supported by the existence of local customs, traditions and wisdom which were always applied in the community activities to meet their household needs.